Combination Of Synthetic Filters With Ultrafiltration For The Treatment Of Cempaka River Water - Hamzani, Sulaiman; A., Syarifudin; Indah Hati, Fatmi; Zubaidah, Tien (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Cempaka District in Banjarbaru City faces a real challenge in meeting clean water needs, due to the river's unfavorable physical characteristics, namely cloudy, brownish water, and frequent flooding and sand and diamond mining activities in the surrounding area. This condition not only reduces the quality and suitability of the water, but also increases health risks due to high levels of sediment, organic matter, and pathogenic microorganisms. The situation is further exacerbated by the limited supply of clean water suitable for consumption, so that the community still relies heavily on river water for daily needs. This study aims to test the ability of a combination of synthetic filters with ultrafiltration (UF) technology to treat Cempaka River water to meet health requirements and support increased access to clean water for the local community. The results show that the use of a combination of DHUSF and UF filters significantly reduced the turbidity of Cempaka River water with an efficiency of more than 95%. Turbidity parameters after treatment were consistently below the established quality standards (<3 NTU). This combination effectively removes suspended and colloidal particles, resulting in clearer and safer water. This system has the potential to be applied at the household or community level, particularly in areas with high levels of river water turbidity. Further studies could test other water quality parameters to optimize the system's implementation.